Effects and mechanisms of Chinese herbal medicine for ulcerative colitis: Protocol for a systematic review and meta-analysis. Issue 16 (April 2020) - Ye, Qiaobo; Hu, Zhipeng; Yang, Maoyi; Qin, Kaihua; Zhou, Yingguang
Abstract: Background: Ulcerative colitis (UC), an important type of inflammatory bowel disease, is mainly characterized by persistent and diffuse inflammatory response of colonic mucosa. Many studies have explored the effects and mechanisms of Chinese herbal medicine (CHM) in UC animal models. However, there is no systematic review and meta-analysis to evaluate and summarize these studies. The purpose of this study is to provide precise evidence of the effects and mechanisms of CHM in treating UC. Methods: Six databases, including 3 English databases and 3 Chinese databases will be searched. Two researchers will independently select eligible studies by reading titles, abstracts, and full texts according to the inclusion and exclusion criteria. Risk of bias assessment will be conducted by 2 independent reviewers using SYRCLE's risk of bias tool. The outcomes include total clinical effective rate, adverse events, disease activity index, interleukin-1β (IL-1β), IL-4, IL-6, IL-17; colombosa damage index, colonic mucosa damage index; myeloperoxidase; epidermal growth factor; transforming growth factor-β1; and histopathological score. Heterogeneity between studies will be assessed by Cochrane X 2 and I 2 tests. We will conduct subgroup analysis to explore the subgroup effects. We will also evaluate the stability of the results through sensitivity analysis and publication bias through funnel plot and Egger test. Results: The results will be published in peer-reviewed journals. Conclusion: This study can help us to understand the effects and possible mechanisms of CHM for UC. For further clinical researches, this study can help us to better look for possible effective medicines for clinical use. OSF registration number: DOI 10.17605/OSF.IO/YU5FN.